Modulable properties of PVA/cellulose fiber composites. Issue 1 (February 2019) - Santi, Romina; Cigada, Alberto; Del Curto, Barbara; Farè, Silvia
Purpose: Development of PVA/cellulose fiber composite material with modulable properties, obtained through the increase of reinforcement and heat treatments in order to optimize the composite in terms of mechanical, thermal, and degradation properties. Methods: The composite was designed selecting as matrix an experimental formulation based on water-soluble, biodegradable, polyvinyl alcohol (PVA) and microcrystalline cellulose (MCC), as reinforcement. Six different formulations, with increasing ratio of MCC content (from 0% to 55% w/w) in PVA, were developed and extruded by a co-rotating twin-screw extruder (TSA FSCM 21/40). Then, samples have been treated through two different thermal conditions (T1, T2) and characterized by scanning electron microscopy, tensile mechanical tests, thermogravimetric analysis, and water degradation tests to investigate, respectively, the influence of MCC ratios and heat treatment on morphological, mechanical, degradation, and thermal properties. Results: The PVA/MCC composite exhibited a good stress–strain behavior as well as a close correlation between MCC content on tensile, thermal, and degradation properties. The second part of the results includes the analysis of the effects that the thermal treatments (T1, T2) had on the composite. In fact, thermal treatments have allowed improving the thermal and water stability as well as a significant improvement in the considered mechanical parameters due to a possible crosslinking of the PVA matrix. Conclusion: The present work shows how the properties of the PVA/MCC composite can become modular with the aim of extending its range of application as a new sustainable solution in the field of consumer products.